Biodiversity Conservation in the Anthropocene: Challenges and Solutions - Fariq, Aiman; Nizam, Zain; Idris, Haziq (Journal of Selvicoltura Asean, 2024)
The Anthropocene epoch is characterized by significant human impact on the Earth's ecosystems, leading to unprecedented biodiversity loss. Rapid urbanization, climate change, and habitat destruction pose severe challenges to conservation efforts. Understanding these challenges is critical for developing effective strategies to preserve biodiversity. This study aims to identify the key challenges to biodiversity conservation in the Anthropocene and propose actionable solutions. By examining current conservation practices and their limitations, the research seeks to highlight innovative approaches that can enhance biodiversity protection. A comprehensive literature review was conducted, analyzing case studies and existing conservation strategies across various ecosystems. The study employs qualitative and quantitative methods to assess the effectiveness of these strategies in addressing biodiversity loss. Findings indicate that habitat degradation, climate change, and invasive species are the primary threats to biodiversity. Successful conservation initiatives, such as community-based management and the establishment of protected areas, demonstrate potential pathways for enhancing biodiversity resilience. Additionally, integrating traditional ecological knowledge with scientific approaches has shown promise in improving conservation outcomes. This research underscores the urgent need for adaptive and collaborative conservation strategies in the Anthropocene. By addressing the identified challenges and implementing proposed solutions, stakeholders can work towards more effective biodiversity conservation, ensuring the protection of ecosystems for future generations.